Conscious and unconscious processes in vision and homeostasis - Fokas, Athanassios S.; Logothetis, Nikos K. (Frontiers in Behavioral Neuroscience, 2025)
The central and autonomic communications affecting cognition, emotions, and visceral functions, are determined by the interaction of unconscious and conscious processes. In this regard, we discuss two basic hypotheses. First, unconscious and conscious processes form a dynamic organizational continuum. Second, emotions, which are unconscious forms of feeling, characterize the response of an organism to any internal change disturbing homeostasis or to any change in the exterior of the organism detected via specialized sensory probes. The former hypothesis is illustrated by discussing aspects of visual perception. The validity of the second hypothesis is supported by discussing interactions between unconscious and conscious process necessary for maintaining energy and water balance.